Thermodynamic, Structural and Surface Properties of Liquid Al-Sr Alloy at Different Temperatures - Oli, P.; Sah, D. K.; Mehta, U.; Gohivar, R. K.; Yadav, S. K. (Adhyayan Journal, 2024)
Thermodynamic functions like excess Gibbs free energy of mixing (∆GxsM) and activity (a) of liquid Al-Sr alloy were studied in the temperature range 1323-1623 K in the frame work of Redlich-Kister (R-K) polynomial. The compositional and temperature dependence of structural functions like concentration fluctuation in long wavelength limit (Scc(0)), Warren-Cowley short range order parameter (α) and ratio of mutual to intrinsic diffusion coefficients (Dm/Did) were computed and analysed using the same approach. The surface tension (σ) and surface segregation (xsi) tendencies of the atoms in the liquid mixture were computed and studied using Butler’s model. Present investigations revealed that association tendency among the atoms of metallic mixture gradually decreased with increase in temperature.